miR-197 Participates in Lipopolysaccharide-Induced Cardiomyocyte Injury by Modulating SIRT1 - Miaomiao Liu; Ying Zhang; Xiantong Cao; Tao Shi; Yang Yan (Cardiology Research and Practice)
Sepsis is a systemic inflammation and is capable of inducing myocarditis, which is a major leading cause of death in patients. Studies have found that miR-197 is correlated with the prognosis of patients with inflammatory heart disease, but its effect on sepsis-induced cardiomyocyte injury remains unclear. We treated H9c2 cells with lipopolysaccharide (LPS), then detected the cell viability via the cell counting kit-8 (CCK-8) assay and quantified miR-197 expression via quantitative real-time polymerase chain reaction (qRT-PCR). Then, we investigated the role of miR-197 in LPS-induced H9c2 cells by CCK-8 assay, flow cytometry, lactate dehydrogenase (LDH) measurement, enzyme-linked immunosorbent assay (ELISA), qRT-PCR, and western blot. Subsequently, silent information regulator 1 (SIRT1) was downregulated in H9c2 cells to explore its interaction with miR-197 under LPS induction. LPS induced miR-197 overexpression in H9c2 cells. LPS restrained viability, the expressions of B-cell lymphoma-2 (Bcl-2) and SIRT1, but promoted apoptosis, LDH release, and levels of interleukin-6 (IL-6), interleukin-1β (IL-1β), acetyl (AC)-p53, BCL2-associated X (Bax), and cleaved caspase-3 in H9c2 cells. miR-197 inhibition reversed the effects of LPS on H9c2 cells. The protective role of miR-197 downregulation in LPS-induced H9c2 cells was reversed by SIRT1 silencing. miR-197 contributed to LPS-induced cardiomyocyte injury by modulating SIRT1, which might be used as a molecular marker in the management of sepsis.